PENGARUH KONSERVATISMA AKUNTANSI TERHADAP RETURN SAHAM YANG DIMODERASI OLEH UKURAN KOMITE AUDIT - Wisnu Haryo Pramudya (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2011)
This research is aimed to answer the problems as well as to tests as to whether: firstly, accounting conservatism affects the return of stocks, secondly, number of audit committee moderates the effect of accounting conservatism to stock return. The total sample consisted of 115 annual reports of 57 companies listed in Indonesia Stock Exchange during the years 2002-2006. Sample was selected using purposive sampling method hypotheses testing and processed using the Moderated Regression Analysis. The results of this research were able to prove the first hypotheses which states that accounting conservatism effects on stock return, and also the effect is significantly negative, and also succeeded in proving the second hypotheses which states that the audit committee moderates the relationship between accounting conservatism with a positive stock return is significant.Keywords: accounting conservatism, stock return, audit committee, company sixe and good corporate governance